2000
DOI: 10.1098/rstb.2000.0670
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence for the Na+/Ca2+exchanger in squid olfactory neurons

Abstract: The olfactory organs from the squid Lolliguncula brevis are composed of a pseudostratified epithelium containing five morphological subtypes of chemosensory neurons and ciliated support cells. Physiological recordings have been made from two of the subtypes and only the type 4 neuron has been studied in detail. Odour-stimulated increases in intracellular calcium and rapid activation of an electrogenic Na+/Ca2+ exchanger current in type 4 neurons suggest that the exchanger proteins are localized very close to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 11 publications
4
17
0
Order By: Relevance
“…Although it is generally accepted that odorant‐elicited [Ca 2+ ] i increases are mediated by an influx of Ca 2+ through the second‐messenger‐gated channels and through voltage‐gated Ca 2+ channels (for review see Schild and Restrepo, ), the mechanism for eliciting an odorant‐elicited decrease in [Ca 2+ ] i is still unknown. There is strong evidence for the involvement of Na + /Ca 2+ exchangers in olfactory neurons (Noe et al, ; Lucero et al, ), which likely mediate Ca 2+ extrusion and the subsequent cellular adaptation following stimulation (Jung et al, ; Reisert and Matthews, , ). Because the mechanisms for driving increases or decreases in [Ca 2+ ] i are very different, it is possible that these mechanisms develop separately and that the mechanism for expression of cellular components for calcium removal from the cytosol is functional prior to the development of second messenger systems (the voltage‐gated channels are developed and functional by day 3, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that odorant‐elicited [Ca 2+ ] i increases are mediated by an influx of Ca 2+ through the second‐messenger‐gated channels and through voltage‐gated Ca 2+ channels (for review see Schild and Restrepo, ), the mechanism for eliciting an odorant‐elicited decrease in [Ca 2+ ] i is still unknown. There is strong evidence for the involvement of Na + /Ca 2+ exchangers in olfactory neurons (Noe et al, ; Lucero et al, ), which likely mediate Ca 2+ extrusion and the subsequent cellular adaptation following stimulation (Jung et al, ; Reisert and Matthews, , ). Because the mechanisms for driving increases or decreases in [Ca 2+ ] i are very different, it is possible that these mechanisms develop separately and that the mechanism for expression of cellular components for calcium removal from the cytosol is functional prior to the development of second messenger systems (the voltage‐gated channels are developed and functional by day 3, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical descriptions of a putative olfactory organ in cephalopods first appeared in early literature (von Kölliker, 1844), followed by more recently demonstrations of their chemosensory capabilities and sensory mechanisms. To date, what is known about the olfactory organ in cephalopods comes from studies of Nautilus (Basil et al, 2000;Ruth et al, 2002) and decapods (Lucero and Gilly, 1995;Lucero et al, 1992Lucero et al, , 2000Mobley et al, 2007Mobley et al, , 2008aPiper and Lucero, 1999;Villanueva and Norman, 2008). In squid the olfactory organ is the site of a sensory epithelium resulted of ciliated supporting cells and different types of receptor cells that are bipolar neurons sending an dendritic stalk branch to the surface of the epithelium where sensory cilia are exposed to the marine environment.…”
Section: Olfaction In O Vulgarismentioning
confidence: 97%
“…Olfaction plays a role in mate choice of squid and cuttlefishes (Cummins et al, 2011;Gilly and Lucero, 1992;Lucero and Gilly, 1995;Lucero et al, 1992Lucero et al, , 2000Mobley et al, 2007;Piper and Lucero, 1999;Zatynly et al, 2000) and improves predation on crabs by cuttlefishes (Boal et al, 2000). Nautilus use olfaction for distant food odour detection and location, and perhaps for mate choice (Basil et al, 2000;Ruth et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…However, single K Ca recordings in membrane patches excised from olfactory cilia showed that in the vicinity of the plasma membrane Ca 2+ may reach much higher values, close to 100 lm (Delgado & Bacigalupo, 2004). Functional evidence indicates that a Na + ⁄ Ca 2+ exchanger (NCX) localizes to the cilia, extruding Ca 2+ after an odour stimulus (Reisert & Matthews, 1998;Danaceau & Lucero, 2000;Lucero et al, 2000).…”
Section: Introductionmentioning
confidence: 97%